An Optimality Theoretic analysis of Yoruba hypocoristic personal names: Issues of truncation, reduplication and tone - Ehineni, Taiwo Oluwaseun (Stellenbosch Papers in Linguistics Plus, 2023)
This paper provides an Optimality Theoretic analysis of Yoruba hypocoristic personal nameswith the aim of showing the interaction of different linguistic processes in the formation ofYoruba names. Based on the data collected from Yoruba texts and interactions in the speechcommunity, this study demonstrates that the formation of the hypocoristics involves not onlyprocesses of shortening or reduplication, but also tonal truncation. While Akinlabi andLiberman (2000) note that Yoruba has tonotactic restrictions—where especially vowel-initialwords can only take a low or mid tone but not a high tone—, this study reveals that suchrestriction may be violated in formation of hypocoristics, where reduplicated forms tend ratherto satisfy a tonal requirement of HHML to be well-formed. Crucially, the study shows thatderiving the hypocoristic in Yoruba involves processes relating not only to the foot structure(foot binarity), where the base of the derived form is expected to be a binary foot, but also, andessentially, processes relating to the tonal structure.